Sharpen Your Sword for Litigation: Incumbent Strategic Reaction to the Threat of Entry - Conti, Annamaria; Ortega, Leonardo; Sung, Elie (Management Science, 2024)
While patents have been shown to play a role as barriers to entry, they also reveal information about incumbent strategies and risk being invalidated. We examine the trade-off incumbents face between using their patents ex ante as entry deterrents or ex post once competitors have revealed their moves. Leveraging the unique characteristics of the pharmaceutical sector, in which it is possible to observe exactly when a competitor entry threat materializes, and exploiting exogenous variation in that timing, we show that incumbents intentionally fragment and delay the full disclosure of their intellectual property rights through continuation patents. They disproportionately reveal continuation patents after a competitor entry threat becomes concrete, tailoring their response to the threat they have received and successfully delaying competitor entry through litigation. The detected incumbents’ reaction is stronger when their attacked drugs are valuable and when the patents listed at the Food and Drug Administration approval of a drug are relatively narrow in scope. This paper was accepted by Alfonso Gambardella, business strategy. Funding: A. Conti acknowledges funding from E4S. E. Sung acknowledges funding from the HEC Foundation [Grant 9B82F1905+] and the U.S. National Science Foundation [Grant 1759991]. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2023.00900 .